(untitled) (Journal of Information Technologies in Education (ITE), 2011)
Annotation of the .U article marketabilities between subject zv’’yazkiv higher mathematics and informatics are exposed at the study of «Rozv’’yazuvannya of spherical triangles» in higher marine educational establishments.